2015
DOI: 10.1186/s12937-016-0131-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and influence factors of vitamin A deficiency of Chinese pregnant women

Abstract: BackgroundVitamin A plays an important role in the periods of rapid cellular growth and differentiation, especially during pregnancy, which is supplied by the mother to the fetus. The aim of this study is to assess the prevalence and potential influence factors of prenatal VAD of Chinese pregnant women.MethodsChina National Nutrition and Health Survey 2010–2013(CHNNS2010–2013) is a nationally representative cross-sectional study. It involved the random selection of 150 districts (urban) or counties (rural). Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
37
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 28 publications
9
37
1
3
Order By: Relevance
“…The findings reported here are similar to those found in China, where a frequency of VAD of 5.2% was found in a group of 1209 pregnant women evaluated in 150 urban or rural areas between 2013 and 2014 [30]. Compared to the present findings, other studies conducted in developing countries using the cut-off point of <0.70 μmol/L reported much higher prevalence rates of VAD in pregnant women: 24.6% in 3270 pregnant women in Iran [31], 20% in a sample of 80 women in Egypt [32], 18.5% in 200 women in Bangladesh [33], 15.8% in 101 women in Nigeria [34], 13.8% in 738 women in Guinea-Bissau [35], and 10.6% in 160 pregnant adolescents in Venezuela [18].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The findings reported here are similar to those found in China, where a frequency of VAD of 5.2% was found in a group of 1209 pregnant women evaluated in 150 urban or rural areas between 2013 and 2014 [30]. Compared to the present findings, other studies conducted in developing countries using the cut-off point of <0.70 μmol/L reported much higher prevalence rates of VAD in pregnant women: 24.6% in 3270 pregnant women in Iran [31], 20% in a sample of 80 women in Egypt [32], 18.5% in 200 women in Bangladesh [33], 15.8% in 101 women in Nigeria [34], 13.8% in 738 women in Guinea-Bissau [35], and 10.6% in 160 pregnant adolescents in Venezuela [18].…”
Section: Discussionsupporting
confidence: 90%
“…Schooling, which has been identified as an important differentiating factor in the results of other surveys on nutrition [30,39,40], was also found to be significantly associated with VAD in the univariate analysis in the present study. Consequently, the prevalence of VAD in the group of women with more than 12 years of schooling was lower.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…However, the baseline serum retinol levels of the study control and supplemented groups were higher than those found in India [31], Africa, [32,33], and Ethiopia [34] as these countries have high prevalence of vitamin A deficiency, and in Germany [35], probably because of the very different sample size. On the other hand, Yang et al [36] reported a higher level of serum retinol possibly because of different diets of the two samples and sampling methods.…”
Section: Discussionmentioning
confidence: 99%